DAKWAH BERBASIS KEBUDAYAAN SEBAGAI UPAYA MEMBANGUN MASYARAKAT MADANI DALAM SURAT AL-NAHL: 125 - Kurdi, Alif Jabal (UIN Sunan Kalijaga Yogyakarta, 2018)
Islam has been present in Indonesia to bring change to a better direction. Islam is not directly accepted by the people of Indonesia. As a step of the initiative of Islamic missionaries in Indonesia, it uses an approach that deals with matters that are inherent in the everyday life of Indonesian society. One of the most effective approaches to spreading Islam is through culture. Indeed, what has been done by Indonesian Islamic preachers reflects the spirit of dakwah, which is recommended by Allah in his word (Q.S. al-Nahl: 125). As a contextualized form of the Rasulullah dakwah method, Islamic preachers in Indonesia have presented Islam really in its context as a religion, not as an Arabic cultural product, as it has recently been misunderstood by some. Through socio-historical-contextual approaches with linguistic analysis based on the interpretation of the scholar's linguistic and social use theory and the use of gratification theory introduced by Herbert Blumer and Elihu Katz, this paper will reveal the values and messages of practice preaching the Prophet to Arab society in his time linked to the practice of dakwah Ulama Indonesia so as to make people aware of the importance of culture in building a civil life, which through culture.Keywords: Dakwah, al-Nahl: 125, Civic Society